A bronze fibula of the Nauheim type discovered in Gura Bâcului (Anenii Noi district, Republic of Moldova) - Iarmulschi, Vasile; Vornic, Vlad (Revista Arheologică, 2025)
In 2012, was submitted to the National Archaeological Agency several metal pieces dating from the Iron Age and Roman period, discovered in different places in the surroundings of the village Gura Bâcului (Anenii Noi, Republic of Moldova). Among them is a ﬁbula of the late La Tène scheme, preserved fragmentarily. The exemplar is attributed to the Nauheim type, dated mainly between the end of the 2nd cent. and 1st century AD. After the presentation of the piece, the closest analogies for the Gura Bâcului clasp are given, with some typological and chronological clarifications.